A Porter’s Five Forces Model Proposal for Additive Manufacturing Technology: A Case Study in Portuguese industry - Dias, Soraya Natalia Sawanga (2022)
Industry 4.0 constituted a trigger to a new phase in the Industrial Revolution, heavily focused on the interconnectivity of the systems, bringing disruptive technologies such as Additive Manufac-turing (AM). On top of that, the shift from an industrial economy to a knowledge-based economy, where knowledge is the actual raw material, implies changes in the labor market, as new jobs strong-ly rely on knowledge-intensive activities. This forces organizations to rethink their way of operating, since markets are getting even more competitive and susceptible to greater volatility. Herewith or-ganizations, are resorting to AM to strengthen their competitive position, as this technology allows them to seize new opportunities. As a response to that, this dissertation presents an industry analysis to AM based on Porter’s Five Forces model, where forces such as the threat of new entrants, bar-gaining power of customers, the threat of substitutes, bargaining power of suppliers and rivalry among the existent competitors will be discussed under a knowledge perspective. To validate the proposed model's practical applicability, a case study was conducted based on a questionnaire that was applied to organizations operating with AM in Portugal. The information collected on the ques-tionnaire supplied the forces of the proposed model. After the analysis was possible to conclude that all the participating firms, except one, fit in the incremental stream of development as regards to Additive Manufacturing technology: Closed-incremental stream, in this stream AM technologies ap-pear as a complementing tool. Regarding the case study results, the participating firms seem to expe-rience the low capability to capture specialized workforce for AM, high capital requirements to enter the market and low IPR regulation. AM brings an opportunity for higher bargaining power to arise due to 'prosumerism', yet it does not add value as a tool for the standard products industry. Moreo-ver, suppliers strongly influence sectors' competition, which will presumably suffer from increased rivalry tensions. For future development, the study of the developed model in a corporate environ-ment where the adoption of the Additive Manufacturing technology is at a more advanced level is suggested.